1994
DOI: 10.1164/ajrccm.149.2.8306026
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lipid composition of bronchoalveolar lavage fluid obtained from individuals with AIDS-related lung disease.

Abstract: Surfactant lipids are not only important to the physiologic function of the lungs, but may also influence disease processes like Pneumocystis pneumonia, in which the interaction of host-defense cells with pathogen occurs within the confines of the surfactant-rich alveolar hypophase. In the present studies the lipid profile of bronchoalveolar lavage fluid (BALF) was characterized in subjects with AIDS-related lung diseases including Pneumocystis pneumonia. BALF lipid and total protein measurements were made in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It is clear that the regulation of the sterol content of P. carinii is important for understanding the growth of the organism. It may be relevant in this regard that other studies from this laboratory have shown significant increases in the amount of cholesterol of bronchoalveolar lavage from human immunodeficiency virus-positive patients (29).…”
Section: Resultsmentioning
confidence: 92%
“…It is clear that the regulation of the sterol content of P. carinii is important for understanding the growth of the organism. It may be relevant in this regard that other studies from this laboratory have shown significant increases in the amount of cholesterol of bronchoalveolar lavage from human immunodeficiency virus-positive patients (29).…”
Section: Resultsmentioning
confidence: 92%
“…Recent reports analysing the surfactant lipids in BAL from HIV-infected pneumonia patients report either reductions [4,5] or abnormalities in lipid composition in these individuals [6]. A study using the rat model found that although the glucocorticoid treatment markedly elevated surfactant lipid levels, these levels were reduced to less than half of untreated control values when the animals became infected with P. carinii [7].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that surfactant-associated protein-A (SP-A) is markedly elevated in bronchoalveolar lavage (BAL) fluid from patients with acquired immune deficiency syndrome (AIDS)-related pneumonias caused by P. carinii [3]. Significant decreases [4,5], or abnormal lipid profiles [6], in surfactant phospholipid levels have recently been reported in BAL from HIV-positive patients. The finding of reduced phospholipids is consistent with experimental observations made in the glucocorticoid-immunosuppressed rat, a model commonly used to study P. carinii pneumonia.…”
mentioning
confidence: 99%
“…Infection results in an interstitial inflammatory response and an eosinophilic proteinaceous alveolar exudate. Previous studies on the pulmonary surfactant system in patients with PCP have yielded inconsistent and fragmentary data (13)(14)(15). In those studies, it was suggested that levels of the hydrophilic surfactant proteins SP-A and SP-D are elevated in bronchoalveolar lavage fluids (BALF) from PCP patients and that the phospholipid profile is altered.…”
mentioning
confidence: 99%